Histologic Characterization of Engineered Tissues in the Canal Space of Closed-apex Teeth with Apical Periodontitis - Gomes Filho, João Eduardo [UNESP]; Tobias Duarte, Paulo Carvalho; Ervolino, Edilson [UNESP]; Bomfim, Suely Regina Mogami [UNESP]; Xavier Abimussi, Caio José; Mota da Silva Santos, Ludmilla; Lodi, Carolina Simonetti; Oliveira, Sandra Helena Penha de [UNESP]; Dezan Junior, Eloi [UNESP]; Cintra, Luciano Tavares Angelo [UNESP] (Elsevier, 2013)
Introduction: The aim of this study was to investigate the capacity of endodontic regenerative procedures combining an induced blood clot, platelet-rich plasma (PRP), and bone marrow aspirate (BMA) to regenerate dental pulp in canine closed-apex necrotic teeth. Methods: Apical periodontitis was induced in 20 upper and lower premolars of 2 dogs. After biomechanical preparation, enlargement to a #60 file, and disinfection with a triantibiotic paste for 28 days, the roots were randomly assigned to 4 treatment groups: blood clot (BC), BC + PRP gel, BC + BMA gel, and BC + BMA/PRP gel. Negative controls were also included. After a 3-month follow-up period, the animals were killed. Results: Histologic analysis showed the presence of newly formed vital tissues (connective, cement-like, and bone-like tissue) in 23 of the 32 treated roots (71.87%). There was no statistically significant difference between the treatment groups. Conclusions: New vital tissues were formed and characterized as connective, cementum-like, or bone-like, but not as pulp-like tissue; PRP and/or BMA did not improve the tissue ingrowth. © 2013 American Association of Endodontists.
Keywords: Bone marrow aspirate; necrotic teeth; platelet-rich plasma; regenerative endodontics; tissue engineering; vital tissue growth